KETERAMPILAN DASAR BERMAIN FUTSAL PESERTA DIDIK DI SMK NEGERI 1 PONTIANAK - Monica, Hervinda; Triansyah, Andika; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract Problems in this study is how big the level of basic skills to play futsal learners who follow extracurricular futsal in SMK Negeri 1 Pontianak. The purpose of research to find out how big skill level of playing futsal learners who follow extracurricular futsal. The method used in this research is survey using measurement. Sampling using total sampling. Samples studied were students who followed extracurricular futsal in SMK Negeri 1 Pontianak as many as 24 people. Data analysis was performed using descriptive analysis using SPSS. The results showed, score for shooting test obtained the lowest score 1.00, the highest score 5.00, the average 2.6667, standard deviation 1.30773. While the score for dribble test obtained lowest score 39.67, highest score 68.11, average 56.65, standard deviation 7.44781. for heading test obtained the lowest score 2.00, highest score 4.00, average 2.3,0417, standard deviation 0.85867. for passing test obtained the lowest score 4.00, highest score 8.00, average 6.0417, standard deviation 1.30148. Students who entered into the medium category are 2 people with percentage of 8.33%, while for the category of less is 5 people with percentage of 20.83%, less category once is 17 people with percentage 70,84%.Keywords: basic skills, futsal, Learners.